2015
DOI: 10.1007/s10967-015-4127-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hydrodynamic suitability of N,N-didodecyl N′,N′-di-octyl diglycolamide: a potential candidate for minor actinide partitioning

Abstract: An unsymmetrical diglycolamide namely N,N, didodecyl-N 0 ,N 0 -dioctyl diglycolamide developed in our laboratory is evaluated for its hydrodynamic suitability by determining the changes in its physical properties such as density and viscosity as a function of temperature and compared with those of tri n-butyl phosphate and N,N,N 0 ,N 0 -tetraoctyl diglycolamide. The effect of irradiation on density, viscosity and interfacial tension, up to a dose of 1000 kGy are also measured. In addition, the activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…170 In particular, D 3 DODGA (Chart 32) was found to be a good compromise, having a high distribution ratio of trivalent Ln(III) and An(III) (D Eu 4 100, D Am 410 at 2 M HNO 3 ) 170 from HNO 3 medium and low D Sr values, and performed well from the hydrodynamic point of view under severe radioactive environment conditions up to 1000 kGy, while not requiring a phase modifier. 171 A series of modifications of the backbone of TODGA revealed that rigidification increased the D values for the extraction of Am(III) and Eu(III), but provided no differentiation between the two metal ions (D values between 5 and 10 at 2 M HNO 3 ). 172 A different arrangement of the structural elements of DGAs Chart 32 (two tertiary amides and an ether group) on a conformationally constrained structure led to the synthesis of 7-oxabicyclo[2.2.1]heptane-2,3-dicarboxamides (OBDA, Chart 33).…”
Section: Malonamidesmentioning
confidence: 98%
“…170 In particular, D 3 DODGA (Chart 32) was found to be a good compromise, having a high distribution ratio of trivalent Ln(III) and An(III) (D Eu 4 100, D Am 410 at 2 M HNO 3 ) 170 from HNO 3 medium and low D Sr values, and performed well from the hydrodynamic point of view under severe radioactive environment conditions up to 1000 kGy, while not requiring a phase modifier. 171 A series of modifications of the backbone of TODGA revealed that rigidification increased the D values for the extraction of Am(III) and Eu(III), but provided no differentiation between the two metal ions (D values between 5 and 10 at 2 M HNO 3 ). 172 A different arrangement of the structural elements of DGAs Chart 32 (two tertiary amides and an ether group) on a conformationally constrained structure led to the synthesis of 7-oxabicyclo[2.2.1]heptane-2,3-dicarboxamides (OBDA, Chart 33).…”
Section: Malonamidesmentioning
confidence: 98%
“…Diamides extractants have attracted widespread attention recently to study the possible use in nuclear fuel reprocessing. Tetraalkyl malonamide [5,6], tetrabutyl succinamide [7,8] and tetrabutyl 3-oxo-diglycolamide [9][10][11] showed good extraction properties for U(VI), Th(IV) and fission products from nitric acid solutions. Mowafy and Mohamed [12] studied the extraction of U(VI) and Th(IV) from nitric acid solutions with N,N,N 0 ,N 0 -tetrabutylsuccinamide (TBSA) in toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Mowafy and Mohamed [12] studied the extraction of U(VI) and Th(IV) from nitric acid solutions with N,N,N 0 ,N 0 -tetrabutylsuccinamide (TBSA) in toluene. Wu et al [9] found that excess of TBSA could react with uranyl to form [UO 2 (TBSA) 3 ] 2? , in which two TBSA ligands were in tridentate mode and the third was in monodentate mode in ionic liquid [Bmim] [NTf2].…”
Section: Introductionmentioning
confidence: 99%